EСOLOGICAL AND MORPHOPHYSIOLOGICAL BASICS OF CROP FORMATION DEPENDING ON THE GROWING DOSES AND METHODS OF FERTILIZERS APPLICATION - Zhailybai K.N.,; Medeuova G.Z.,; Nurvash N.K., (Academic Journal of Physical and Chemical Sciences, 2021)
Highly productive barley agrocenosis is formed when plants are preserved before harvesting 240-260 pcs/m2 , formation of productive stems 640-680 pcs/m2 , with bushiness of 2.70-2.85 pcs/plant, the proportion of lateral shoots in crop formation was 62.4-64.8%. This contributed to an increase in grain yield to 33.1- 36.7 centner/hectare, the yield increase was 17.7-21.3 centner/ viable seeds are sown and N90P90 kg/ha is added prior to sowing and additional fertilizing with nitrogen fertilizer N30 kg/ha in the beginning of tillering period, irrigation mode 70-75-70% of the total field moisture-holding capacity (MHC) and in the course of other agronomic techniques of due quality in due time